What is the y-value of the vertex of the function f(x) = –(x + 8)(x – 14)?
1 answer:
we have
![f(x)=-(x+8)(x-14)](https://tex.z-dn.net/?f=f%28x%29%3D-%28x%2B8%29%28x-14%29)
Convert to vertex form
![f(x)=-(x+8)(x-14)\\f(x)=-( x^{2}-14x+8x-112) \\f(x)=-( x^{2}-6x-112)\\f(x)=-x^{2}+6x+112](https://tex.z-dn.net/?f=f%28x%29%3D-%28x%2B8%29%28x-14%29%5C%5Cf%28x%29%3D-%28%20x%5E%7B2%7D-14x%2B8x-112%29%20%5C%5Cf%28x%29%3D-%28%20x%5E%7B2%7D-6x-112%29%5C%5Cf%28x%29%3D-x%5E%7B2%7D%2B6x%2B112)
we know that
the equation of a vertical parabola in vertex form is equal to
![y=a(x-h)^{2} +k](https://tex.z-dn.net/?f=y%3Da%28x-h%29%5E%7B2%7D%20%2Bk)
where
(h,k) is the vertex
![f(x)=-x^{2}+6x+112](https://tex.z-dn.net/?f=f%28x%29%3D-x%5E%7B2%7D%2B6x%2B112)
Group terms that contain the same variable, and move the constant to the opposite side of the equation
![f(x)-112=-(x^{2}-6x)](https://tex.z-dn.net/?f=f%28x%29-112%3D-%28x%5E%7B2%7D-6x%29)
Complete the square. Remember to balance the equation by adding the same constants to each side
![f(x)-112-9=-(x^{2}-6x+9)](https://tex.z-dn.net/?f=f%28x%29-112-9%3D-%28x%5E%7B2%7D-6x%2B9%29)
![f(x)-121=-(x^{2}-6x+9)](https://tex.z-dn.net/?f=f%28x%29-121%3D-%28x%5E%7B2%7D-6x%2B9%29)
Rewrite as perfect squares
![f(x)-121=-(x-3)^{2}](https://tex.z-dn.net/?f=f%28x%29-121%3D-%28x-3%29%5E%7B2%7D)
![f(x)=-(x-3)^{2}+121](https://tex.z-dn.net/?f=f%28x%29%3D-%28x-3%29%5E%7B2%7D%2B121)
the vertex is the point ![(3,121)](https://tex.z-dn.net/?f=%283%2C121%29)
therefore
<u>the answer is </u>
The y-value of the vertex is ![121](https://tex.z-dn.net/?f=121)
You might be interested in
Answer:
S i neorrddints poy
Step-by-step explanation:asdadasdasdasdo
Answer: obtuse
Step-by-step explanation:
Answer:
9
Step-by-step explanation:
3x + 3 = 30
-3 -3
3x = 27
/3 /3
x= 9
There both in the thousands place